2022
DOI: 10.1016/s2666-5247(21)00266-4
|View full text |Cite
|
Sign up to set email alerts
|

WHO International Standard for evaluation of the antibody response to COVID-19 vaccines: call for urgent action by the scientific community

Abstract: The first WHO International Standard and International Reference Panel for anti-SARS-CoV-2 immunoglobulin were established by the WHO Expert Committee on Biological Standardization in December, 2020. The WHO International Antibody Standards are intended to serve as global reference reagents, against which national reference preparations or secondary standards can be calibrated. Calibration will facilitate comparison of results of assays (eg, of the neutralising antibody response to candidate COVID-19 vaccines)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 18 publications
2
132
0
Order By: Relevance
“…We have previously shown that although serum antibodies against the RBD of the S protein of SARS-CoV-2 are markedly reduced 6-12 months after infection, long-lived B and T cell memories persist for up to 15 months and may thus aid in resistance against re-infection 22,23 . Here, we show that the decline of the serum antibody levels was more rapid in the vaccinated individuals compared to naturally infected patients, supporting and extending previous findings 24, 25 . This raises the question on strategies for boosting the immune response in vaccine recipients, which is of particular concern in view of the limited induction of cross-neutralizing antibodies against the Omicron VOC even by the mRNA vaccines [26][27][28][29][30][31] .…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that although serum antibodies against the RBD of the S protein of SARS-CoV-2 are markedly reduced 6-12 months after infection, long-lived B and T cell memories persist for up to 15 months and may thus aid in resistance against re-infection 22,23 . Here, we show that the decline of the serum antibody levels was more rapid in the vaccinated individuals compared to naturally infected patients, supporting and extending previous findings 24, 25 . This raises the question on strategies for boosting the immune response in vaccine recipients, which is of particular concern in view of the limited induction of cross-neutralizing antibodies against the Omicron VOC even by the mRNA vaccines [26][27][28][29][30][31] .…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition signal from individual samples from the cPass assay was converted to the World Health Organization (WHO) International Units (IU) based on previous calibration of this neutralization assay against the WHO International Standard (IS) for SARS-CoV-2 neutralization assays ( 21 , 22 ), using a Excel-based conversion tool available online ( ). Based on recent studies using biological replicates from different international groups, cPass readings (% inhibition) were shown to be highly reproducible to International Units (IU)/ml of the WHO International Standard, with a pseudo R 2 at 0.978. cPass inhibition signal of 30% corresponds to a cut-off of 28 IU/ml for serum samples and 7 IU/ml for breastmilk samples based on the conversion to WHO International Standard and dilution factor for sample type.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition signal from individual samples from the cPass assay was converted to the World Health Organization (WHO) International Units (IU) based on previous calibration of this neutralization assay against the WHO International Standard (IS) for SARS-CoV-2 neutralization assays (21,22), using a Excel-based conversion tool available online (https://github. com/Lelouchzhu/cPass-to-IU_Conversion).…”
Section: Sars-cov-2 Surrogate Viral Neutralization Assaymentioning
confidence: 99%
“…Indeed, in the current pandemic a large number of serological tests, based on different technologies and recognizing different epitopes of the S-protein, have been used along with neutralization assays. Even if an international standard for the evaluation of the antibody response to COVID-19 has been released by the WHO [13], its utility in enabling comparability of binding antibody tests has been criticized [14,15] and its use for standardization of neutralizing antibodies assays is still limited to few laboratories [13].…”
Section: Introductionmentioning
confidence: 99%